Examination of Marketing Communication Tactics to Enhance Brand Recognition for BSKIN Aesthetic Products - Stephany Hildegard Yuandesta; Ratna Puspita Sari (DIGICOM : Jurnal Komunikasi dan Media, 2023)
According to data from the Central Statistics Agency (BPS), in 2021 there will be an increase of 9,61% in the growth of the chemical, pharmaceutical and traditional medicine industry, especially in the production and sale of cosmetics. BSkin is present in Indonesia as a facial care product originating from Korea and competes with other facial care products. This study aims to analyze the marketing communication strategies that have been used by BSkin in an effort to increase brand awareness of their aesthetic products. In this study used a qualitative descriptive method. The results obtained from the research are that BSkin has carried out integrated marketing communication strategies to increase brand awareness of its products among the public, including using social media and digital media as marketing media, publishing on online media and print media, using promotional tools such as vouchers, catalogs, booklets, discount promos, free product promotions, sweepstakes, cashback, Instagram challenges, royalty rewards. BSkin also holds meetings and participates in large-scale beauty events to introduce BSkin to the public. The conclusion that can be drawn is that the strategy that has been carried out by BSkin has succeeded in getting people to know BSkin and making BSkin top of mind.